Are Real Wages Rigid Downwards? - Steinar Holden; Fredrik Wulfsberg (Norges Bank, 2007)
This paper explores the existence of downward real wage rigidity (DRWR) in 19 OECD countries, over the period 1973-1999, using data for hourly nominal earnings at industry level. Based on a nonparametric statistical method, which allows for country and year specific variation in both the median and the dispersion of industry wage changes, we find evidence of some downward rigidity of real wages in OECD countries overall, as well as for regions and time periods. There is some evidence that real wage cuts are less prevalent under strict employment protection legislation and high union density. Generally, we find stronger evidence for downward nominal than for downward real wage rigidity.
hdl:11250/2498277
Keywords: J3; J5; C14; C15; E31; 330; OECD; downward real wage rigidity; employment protection legislation; wage setting